Analisis Keberhasilan Video Pembelajaran Sparkol Videoscribe Pada Materi Trigonometri - Aurora, Stefani; Samijo; Sulistyono, Bambang Agus (Papanda, 2025)
This research aims to analyze the effectiveness of the learning media, namely Sparkol Videoscribe learning videos, in improving students understanding of trigonometry material. This research falls under the category of descriptive qualitative research. The research subjects were eleventh-grade students at SMAN 1 Pelemahan. The sample consisted of 28 students from a single class. The sample was selected based on their knowledge of trigonometry learning material.The instruments used in this research were students pre-test and post-test results, which were used to analyze the effectiveness of the Saprkol Videoscribe learning media/ the data analyze technique used in this research involved first reducing the data, then presenting it according to the need of the research, and finally drawing conclusions based on the data, based on the test results, student were grouped into three categories : high, medium, and low. The improvement in students understanding can be seen through the results of the students post test grouping specifically, whether there are changes in each students category. If there are change, then this research can be aid to improve students understanding of trigonometry material through the use of Sparkol Videoscribe learning videos as the learning media .In this research, each subject showed improvement through the results of the pre-test and post-test, as well as in the categorization of their level of understanding. However, this research is not without its limitations, and threfore the future researchers are expected to explore information more thoroughly and presentthe data more effectively